Abundance and Diversity of Bryofauna in Coffee and Tea Vegetations - Rahadian, Rully; Perwati, Lilih Khotim; Baskoro, Karyadi (Bioma : Berkala Ilmiah Biologi, 2016)
Forest alteration into agroecosystem affect many organisms including bryofauna which their survivorship depend much on their host. Coffee and tea plantation are common agroecosystem in Indonesia. So far, the effect of habitat alteration on Bryofauna community have not been known yet. The objective of this study is to determine community structure attributes i.e., abundance, diversity and composition of bryofauna living in coffee and tea vegetation. The study was located in Ungaran Mountain, District of Semarang Indonesia. Bryofauna were extracted from moss using Tullgren funnel method and were identified until possible taxa. Bryofauna sampling was conducted both in coffee and tea vegetation. Bryofauna were extracted from the moss using Tullgren funnel method. The result shows that Acari was the most abundant both in coffee and tea area. Generally, bryofauna was more abundant in the coffee vegetation than in the tea vegetation. The diversity of bryofauna was not affected neither by altitude nor vegetation. However, the diversity of bryofauna seems affected more by their host, bryophyte.Â Keywords: Bryofauna, Acari, coffee and tea vegetation.